The Production Process for the Song “Detroit” by the Band The Flins Tone in the Independent Music Industry - Demas Labib Azzaki (Repertoar, 2026)
The purpose of this study is to explain the process of creating and recording the song “Detroit” by the band The Flins Tone. This process will be discussed through an analysis of the production and recording processes, based on the theories of Arnold Schoenberg, Hepworth-Sawyer, and Golding. The research method used in this study is qualitative descriptive research through direct observation, structured interviews, and documentation. The data analysis techniques in this study include data collection, data reduction, data presentation, and conclusion. After data collection, they were validated through source and technique triangulation. This study consists of two parts: first, the creative production process, which includes pre-production for the song “Detroit”—involving the development of a conceptual outline and an understanding of each member’s role; developing variations by refining the existing ideas to serve as a final guide; and combining practical exercises with spontaneous studio rehearsals to foster communication and improvisation among members; followed by the recording process, which involved recording all stages in accordance with the theme of the song “Detroit,” and post-production, which refined the audio from the recorded material to prepare it for distribution.